Photovoltaic Energy-Assisted Electrocoagulation of a Synthetic Textile Effluent - Thelma Beatriz Pavón-Silva; Hipólito Romero-Tehuitzil; Gonzálo Munguia del Río; Jorge Huacuz-Villamar (International Journal of Photoenergy)
The feasibility of using photovoltaic modules to power a continuous 14 L electrochemical reactor applied to remove an azo dye with an efficiency of 70% is reported. The photovoltaic modules were directly connected, and the system efficiency was observed properly maintained when currents were applied in the range of 2.5 to 7.9 A. This value depends on solar radiation. Likewise, it was found that the efficiency depends mainly on the current density and the flow rate prevailing in the reactor.